2020
DOI: 10.1111/pce.13743
|View full text |Cite
|
Sign up to set email alerts
|

Temperature responses of photosynthesis and leaf hydraulic conductance in rice and wheat

Abstract: Studies on the temperature (T) responses of photosynthesis and leaf hydraulic conductance (K leaf ) are important to plant gas exchange. In this study, the temperature responses of photosynthesis and K leaf were studied in Shanyou 63 (Oryza sativa) andYannong 19 (Triticum aestivum). Leaf water potential (Ψ leaf ) was insensitive to T in Shanyou 63, while it significantly decreased with T in Yannong 19. The differential Ψ leaf − T relationship partially accounted for the differing g m -T relationships, where g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 66 publications
2
29
0
Order By: Relevance
“…Normalized temperature responses of mesophyll conductance, g m . Multiple responses are shown for rice (a) and wheat (b) (Scafaro et al ., 2011; von Caemmerer & Evans, 2015; Li et al ., 2020; Yang et al ., 2020), a diverse range of C 3 species (c) (von Caemmerer & Evans, 2015) and C 4 species (d) (Ubierna et al ., 2017). For each response, g m values were normalized relative to the value measured at 25°C.…”
Section: Temperature Responses Of Gmmentioning
confidence: 99%
“…Normalized temperature responses of mesophyll conductance, g m . Multiple responses are shown for rice (a) and wheat (b) (Scafaro et al ., 2011; von Caemmerer & Evans, 2015; Li et al ., 2020; Yang et al ., 2020), a diverse range of C 3 species (c) (von Caemmerer & Evans, 2015) and C 4 species (d) (Ubierna et al ., 2017). For each response, g m values were normalized relative to the value measured at 25°C.…”
Section: Temperature Responses Of Gmmentioning
confidence: 99%
“…In liquids such as water, this friction decreases with increasing temperature, due the increase of thermal energy of water molecules enabling them to overcome the attraction of other molecules from adjacent layers of flow (Kestin, Sokolov, & Wakeham, 1978; Seeton, 2006; Figure 2). Changes in water viscosity have been invoked to partially explain temperature‐mediated increases in leaf transpiration rate (Fredeen & Sage, 1999; Matzner & Comstock, 2001; Sack & Holbrook, 2006; Yang, Zhang, Huang, Peng, & Li, 2020). For instance, Fredeen and Sage (1999) found that decreases in water viscosity explained half of the increase in leaf transpiration rate in white spruce resulting from increases temperature from 10 to 35°C, and a similar finding was established by Yang et al (2020) on rice and wheat in the 15 to 40°C range.…”
Section: Effect Of High‐temperature Stress On Crop Water Usementioning
confidence: 99%
“…Recent advances in omics technologies and gene transformation have allowed genetic analyses to investigate the molecular mechanisms of plant development, ecology, and evolution [3,170]. Recent works also have made great breakthroughs in the fields of environmental signals sensing [171][172][173], phytohormone interactive networks [29], and plant stress combinations [174,175]. Until now, the molecular mechanisms underlying leaf development have been extensively elucidated [114,176].…”
Section: Future Perspectivesmentioning
confidence: 99%